P-239 Giving praise where praise is due: learning from excellence in a hospice. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Radcliffe, Christina; Talbot, Deborah; Clarke, Wendy; Beale, Shirley
Abstract : Background: Healthcare settings have traditionally focused on developing safe systems by learning from incidents and errors (Kelly, Blake & Plunkett, 2016). Considerable time and energy is spent on activities including incident reporting and root cause analysis, whilst less attention is paid to the majority of times when things go well (NHS England, 2015). Birmingham St Mary's Hospice introduced a system of Learning from Excellence (https://learningfromexcellence.com/) to address this. We hypothesised that this would improve staff morale and retention, provide evidence of good practice for team learning, quality reports and marketing and be useful for team appraisal and revalidation. Aim: To institute a learning from excellence scheme within the hospice setting, across all hospice teams. We describe the set up process and support needs for this project. Method: Support was obtained from the executive team. A small task and finish group was set up. Having accepted advice from other local healthcare providers, a simple form was generated. An IT apprentice supported the team to generate an electronic version of the form which was intranet based. A paper version was used where preferred. A volunteer was recruited to support the initiative. A soft launch was conducted and forms invited with the task and finish group encouraged to role model by reporting. Initially all reports were overseen by a consultant in palliative medicine, with anticipated handover to volunteer and administrative team. Recipients were provided with a response on headed notepaper to allow use in appraisal. Results: Forms have been analysed and themes generated. Informal feedback has been sought from staff who have completed and received LfE reports. Conclusions: Learning from excellence has been a positive experience, allowing us to focus on what is done well within the hospice setting. Some aspects of set up have been novel within our hospice and we recommend more widespread use within hospices.